Answer:
11 A. p-r=x B. a+b+c=x C. x=z-3y D. x=2p E.
=x F. x=p+2mn
12 A.
=y B.y=
C.
=y D.
=y E. y=
F.y=
![(r)/(6.14)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2fca03s19g0yhufijv9sfjjyell3lr2qjj.png)
Step-by-step explanation:
11. a.For all I did was to eliminate r on one side by subtracting it and doing it to the other side and get x by itself
b. This equation I just added c on both sides and got x all by itself and got a+b+c=x
c. I subtracted 3y on both sides to leave x by itself and get x=z-3y
d. I combined like terms and since I subtract 3p to cancel it off and I do it to the other side and combine 5p and -3p and get 2p and to finalize it my answer was x=2p
e. Same process as the last equation I combine like terms and
+a itself is
so
f.on this one I would also combine like terms since there are 2 mn's so I would cancel out -mn by adding mn and doing it to the same side and mn+mn=2mn, and no changes to p so x=p+2mn.
12. A.any variable attached to another variable is a sign of multiplication, so I can do the inverse to get y itself by dividing by n and do the same to the other side.
=y.
B. I divided b^2 from b^2y and did it on both sides, and my new answer will be y=
C. to get y by itself, I need to divide q on both sides but the most important thing is what im gonna divide q by and that's p+3 so when I do that I get
=x
D. first I subtracted h on both sides and the new equation is g-h=fy. But I'm not done yet because y is still not by itself. So now I will divide f on both sides and get
=y.
E. Same method as last time we just divide the variables on both sides. ab divided on both sides and my final equation will be y=
.
F. This one seems more complex in terms of strategizing this out. So what I did is that I used the distributive property for y(
+2) and when solving it out I got 3.14y+2y=r. Now, I can combine the like terms and solve for y after. 3.14y+2y=6.14y. I can divide 6.14 on both sides to get y by itself and my final answer will be y=
.